Drivers, Challenges, and Support of Student Entrepreneurship at the University of Lagos, Nigeria - Aladejebi, Olufemi; Amao-Taiwo, Bukola (Archives of Business Research, 2023)
Universities have been known to declare the intention to graduate students who are entrepreneurial and innovative in ways that spur socio-economic development. However, the outright increase in the rate students pursue white-collar jobs and delist from active entrepreneurial life has become alarming. There is more to student entrepreneurship development than teaching courses and setting up entrepreneurship centres. This study adopted a mixed-method approach to explore the drivers, challenges, and support available for student entrepreneurs at the University of Lagos. The study employed qualitative and quantitative methods to gather data from 15 students (*10 randomly selected through the university entrepreneurship centre and five students yet to engage with the university entrepreneurship centre). A researcher-designed open-ended questionnaire and key informant interview guide were used to gather data from the respondents. Responses from the questionnaire were synthesized and converted to quantitative data manually. In contrast, responses from the key informant interviews were coded into themes and stated verbatim in line with the study's objectives. The results showed that the craving for financial independence was the top of the reasons why students engage in entrepreneurship. In contrast, the inability to combine entrepreneurship with school activities served as one of the major challenges for student entrepreneurs. However, student entrepreneurs also need help with significant challenges, such as lack of funding, lack of support from the University, and difficulty balancing academic demands with entrepreneurial pursuits. The study also recommends that the university timetable and yearly schedule be designed to allow student entrepreneurs to balance their academic responsibilities with the demands of their businesses. Overall, the findings of this study have implications for universities, policymakers, and other stakeholders.